ISOLASI DAN KARAKTERISASI GELATIN DARI TULANG AYAM DENGAN METODE ASAM - Jannah, Akyunul; Maunatin, Anik; Windayanti, Arin; Findianti, Yuana; Mufidah, Zulfiatul (ALCHEMY, 2013)
The purpose of this study was to determine the quality of gelatin by using raw materials bone chicken (Gallus gallus domesticus) and the Broiler chickens for differences in the concentration of acetic acid immersion process ( curing ).The method used in this study is the preparation and broiler chicken bones , isolation of gelatin with various concentration of acetic acid in the curing process , the process of hydrolysis , extraction temperature rise and gelatin with gelatin obtained include the characterization of protein , water , ash and metal.The results showed the highest yield of gelatin produced from Broiler chicken bone types with acetic acid concentration of 1 % , ie 3.25%. Gelatin highest protein content of 86.27 % of the types of Broiler chicken bone with acetic acid concentration of 1.5 %. Lowest ash content of 15.7 % gelatin from bone types Broiler chicken with 1 % acetic acid concentration , and from analysis using AAS contained Cu at 0.6 % (of the type of chicken bones, acetic acid concentration of 0.5 %) and Cu metal content of 1.1 % (of the type of Broiler chicken bones, acetic acid concentration of 1 %. highest moisture content of 0.17 % gelatin from bone types Kampung chicken with 1 % acetic acid concentration